PENGARUH KEPUASAN KERJA, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP LOYALITAS KARYAWAN PT. BARAKA SARANA TAMA - Bilady, Royhan; Recky, Recky; Ismail, Gurawan Dayona; Nazarudin, Nazarudin (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This study aims to analyze the impact of job satisfaction, work discipline, and work motivation on employee loyalty at PT. Baraka Sarana Tama. The research uses a quantitative approach with descriptive and verificative methods, and data collection techniques are conducted cross-sectionally. Data analysis is performed using Partial Least Square (PLS-SEM). The sample consists of 90 employees selected through Simple Random Sampling. The results show that job satisfaction, work discipline, and work motivation have a positive and significant effect on employee loyalty. Work discipline and work motivation are found to have a more significant impact on loyalty, with high discipline and strong motivation playing an essential role in increasing employees' commitment to the company. These findings emphasize that companies focusing on improving job satisfaction, recognizing achievements, and providing career development opportunities are more successful in building a loyal and dedicated team. This study also suggests that companies should ensure fair and consistent application of work discipline to support employee loyalty. Keywords: Job Satisfaction, Work Discipline, Work Motivation, Employee Loyalty, SEM PLS